Topological spatial relations between a spatially extended point and a line for predicting movement in space - Santos, Maribel Yasmina (2007)
Location is an important dimension of contextual information for mobile systems, playing a key role in the development of context-aware and location-based applications. The identification of a specific location is well addressed by several existing technologies such as, for example, GPS (Global Positioning System). Moreover, the prediction of the next position of a mobile user is a valuable enabler for the development of pro-active location-based applications. Based on this knowledge, those applications become able to provide useful services for the users before they explicitly ask for them. As a step towards the prediction of the next position of a mobile user, this paper presents the identification of the topological spatial relations that can exist between a spatially extended point (representing the uncertainty on the position of a mobile user) and a line (representing objects in which movement in space is possible). Using a 4x3 intersection matrix we identified 38 topological spatial relations that can exist between the objects in analysis (spatially extended points and lines). The geometric realization of the 38 topological spatial relations was done through the analysis of each one of the identified valid matrices. The validation of the existence of the identified topological relations was verified from their geometric realization.